2021
DOI: 10.1101/2021.02.27.21252099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent SARS-CoV-2 infection and increasing viral variants in children and young adults with impaired humoral immunity

Abstract: Background There is increasing concern that persistent infection of SARS-CoV-2 within immunocompromised hosts could serve as a reservoir for mutation accumulation and subsequent emergence of novel strains with the potential to evade immune responses. Methods We describe three patients with acute lymphoblastic leukemia who were persistently positive for SARS-CoV-2 by real-time polymerase chain reaction. Viral viability from longitudinally-collected specimens was assessed. Whole-genome sequencing and serologica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…There have been relatively few published descriptions of persistent SARS-CoV-2 infection, the majority associated with B cell immunodeficiency (7,10,27,(41)(42)(43)(44). Conversion to PCR negativity and dramatic symptomatic improvement was achieved only after administration of casirivimab and imdevimab.…”
Section: Discussionmentioning
confidence: 99%
“…There have been relatively few published descriptions of persistent SARS-CoV-2 infection, the majority associated with B cell immunodeficiency (7,10,27,(41)(42)(43)(44). Conversion to PCR negativity and dramatic symptomatic improvement was achieved only after administration of casirivimab and imdevimab.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations are located in three distinct hotspots -N-terminal domain (NTD), receptorbinding domain (RBD), and Furin cleavage site (Figure 2A). Mutation E484K was present in the highest number of unrelated lineages [11, Table 1], followed by L452R [10], P681H [9], Y144Δ [8], HV69-70Δ [6], Q677H [6] and N501Y [6]; these mutations thus display the strongest convergent evolution. The overall load of convergent mutations in the S-protein was quantified (lineage parallelism score, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The mutations that do not follow this trend are L452R, F490S, T478K, and S494P; we thus speculate that their benefits for viral fitness are likely connected with the host immune system. The immunocompromised patients, treated or non-treated with convalescent plasma or neutralizing antibodies, have been regarded crystal balls for prediction of viral evolution (7,8), showing the emergence of N501Y, S494P, Q493K, Y489H, E484K, T478K and N440D (9, 10) variants during infection. Surprisingly, only mutations E484K and N501Y arose convergently among patients, and their emergence was restricted to a low number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some studies have shown that selective pressure from therapeutic mAbs or convalescent serum could induce E484K or E484Q mutations 26,27 . These results indicate the importance of E484 in the viral epitope.…”
Section: Discussionmentioning
confidence: 99%